Retrospective Assessment of Movement Disorder Society Criteria for Mild Cognitive Impairment in Parkinson's Disease - Loftus, A.; Bucks, R.; Thomas, M.; Kane, Robert; Timms, C.; Barker, R.; Gasson, Natalie (Cambridge University Press, 2015)
A Movement Disorder Society (MDS) taskforce recently proposed diagnostic criteria for Parkinson's disease with features of mild cognitive impairment (PD-MCI). This study first examined the prevalence and nature of PD-MCI in a non-demented cohort using the MDS criteria. Using the generic Monte Carlo simulation method developed by Crawford and colleagues (2007), this study then estimated the base rate of the representative population who would demonstrate PD-MCI due to chance alone. A total of 104 participants with idiopathic PD underwent extensive motor and neuropsychological testing at baseline and 2 years later. The Unified Parkinson's Disease Rating Scale (UPDRS) was used to assess motor symptoms of PD and a range of established neuropsychological tests was used to assess PD-MCI in accord with MDS criteria. In accord with MDS criteria, 38% of this cohort demonstrated PD-MCI at baseline and 48% at follow-up. Of the 36 participants in the multiple-domain PD-MCI subtype at time-1, 9 (25%) demonstrated no PD-MCI at follow up. Analysis revealed that approximately 13% of the representative population would demonstrate abnormally low scores for 2 of the 9 tests used, thereby meeting MDS criteria for PD-MCI. Clinicians and researchers need to approach a single diagnosis (i.e., based on one assessment) of PD-MCI with considerable caution.